Optimization of NFRP Turbine Blade Material on The Harper Malioboro Hetel Ballroom Ventilator Through Design Analysis - Ahmad Satria Wibowo; Ardani Ahsanul Fakhri (Program Studi Sarjana Terapan Teknik Mesin, Fakultas Vokasi, Universitas Negeri Yogyakarta, 2026)
This study aims to evaluate the performance of natural fiber-reinforced polymer (NFRP) composite material as an alternative to aluminum AA1100 for turbine ventilator blades, considering aluminum's limitations in sustainability. Numerical simulations were conducted using ANSYS Workbench 2025 R1, applying variations in fiber reinforcement combinations (Low, Mid, High) and fiber orientations (Bidirectional, Unidirectional, Random). The turbine blade design was visualized as a 3D model using Autodesk Inventor 2024. Analysis parameters included maximum stress (von Mises), total deformation, fatigue life, and equivalent alternating stress. Results showed that the Mid–Random configuration yielded the most optimal performance, with a maximum stress of 22.009 MPa, total deformation of 6.7009 mm, fatigue life reaching 5.3698 × 10⁵ cycles, and an equivalent alternating stress of 9.0395 × 10³¹ Pa. This configuration also outperformed aluminum in terms of fatigue resistance. Based on these findings, the Mid–Random NFRP material is recommended as an environmentally friendly alternative for turbine ventilator blade applications.